The effectiveness of STEM Project-Based Learning in improving students' environmental literacy abilities - Tasya Umi Pertiwi; Dwi Oetomo; Bowo Sugiharto (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
This study aimed to determine the difference in environmental literacy skills between the Project-Based Learning (PjBL) learning model and STEM-based PjBL. This research is quantitative research with a quasi-experimental method. The research design used is a non-equivalent pretest-posttest control group design. The dependent variable in this study is environmental literacy skills. The population in this study were all grade X students of State Senior High School (SHS) 7 of Surakarta in the 2023/2024 academic year. The sampling technique used was cluster random, tenth grade (X) A and B. A class consists of 36 students, as a control, using the PjBL model whereas as many as 35 students in B class is an experimental group was learned using the STEM-PjBL model. The data collection technique was carried out using pretest and posttest on the research sample. Data analysis technique using ANCOVA test. Instrument validation techniques using validity tests and reliability tests. The test results using ANCOVA have a significance value of <0.05, indicating differences in students' environmental literacy skills between the implementation of PjBL and STEM-PjBL. These results show that implementing the STEM-PjBL model was superior compared to PjBL only. It can be seen from the difference in learning outcomes of the control class, within the pretest and posttest, which showed an increase of 10.16%. In comparison, the experimental class results showed an increase of 16.94%. STEM-PjBL also helps students to be able to improve their environmental literacy skills in terms of knowledge, cognitive skills, attitudes, and behavior toward environmental problems.